(untitled) (Economics and region, 2018)
The causes of the occurrence and spread of corruption are considered. The level of perception of corruption in Ukraine is analyzed according to the data of the international anti-corruption organization Transparency International. The corruption component of the national economy is investigated in various spheres: material production, finance, transport, procurement, land management, non-material production, public administration, etc. It was revealed that corruption in the field of land relations and miscalculations in land policy provoked the emergence of shadow land relations and the shadow land market in Ukraine. The consequences of the influence of corruption on the safe economic development of the national economy are determined. It is substantiated that the corruption threat significantly weakens the country’s economic security and is a real threat to the national security of Ukraine as a whole. A number of unresolved problems that arose as a result of the corruption component and hinder the transition of Ukrainian economy to the innovative way of development are outlined. Models of specialized anti-corruption institutions are explored. The experience of Singapore and Hong Kong (where the first specialized anti-corruption bodies were created) are best known in this area, and these institutions are associated with the effective instrument of an effective, independent, multi-purpose anti-corruption body. It is proved that the main model of the fight against corruption in Ukraine should be the European model with the application of elements of Asia in the form of inevitability of punishment of a crime. Organizational and economic measures to combat corruption in the framework of ensuring economic security of the state are allocated. The authors determined that proceeding from the difficult state of the real sector of the Ukrainian economy, counteracting the corruption threat to the economic security of the state should have a comprehensive and systematic character by optimally combination of the processes of public administration and social self-organization and management.